Efficacy and safety of continuous 4-year telbivudine treatment in patients with chronic hepatitis B - Y. Wang (2018)
In the phase-III GLOBE/015 studies, telbivudine demonstrated superior efficacy vs lamivudine during 2-year treatment in HBeAg-positive and HBeAg-negative chronic hepatitis B (CHB). After completion, 847 patients had an option to continue telbivudine treatment for further 2 years. A total of 596 (70%) of telbivudine-treated patients, who were serum HBV DNA positive or negative and without genotypic resistance to telbivudine at the end of the GLOBE/015 trials, were enrolled into a further 2-year extension study. A group of 502 patients completed 4 years of continuous telbivudine treatment and were included in the telbivudine per-protocol population. Amongst 293 HBeAg-positive patients, 76.2% had undetectable serum HBV DNA and 86.0% had normal serum ALT at the end of 4 years. Notably, the cumulative rate of HBeAg seroconversion was 53.2%. Amongst 209 HBeAg-negative patients, 86.4% had undetectable HBV DNA and 89.6% had normal serum ALT. In patients who had discontinued telbivudine treatment due to HBeAg seroconversion, the HBeAg response was durable in 82% of patients (median 111 weeks of off-treatment follow-up). The cumulative 4-year resistance rate was 10.6% for HBeAg-positive and 10.0% for HBeAg-negative patients. Most adverse events were mild or moderate in severity and transient. Renal function measured by estimated glomerular filtration rate (eGFR) increased by 14.9 mL/min/1.73 m2 (16.6%) from baseline to 4 years (P < 0.0001). In conclusion, in HBeAg-positive and HBeAg-negative CHB patients without resistance after 2 years, two additional years of telbivudine treatment continued to provide effective viral suppression with a favourable safety profile. Moreover, telbivudine achieved 53% of HBeAg seroconversion in HBeAg-positive patients. © 2012 Blackwell Publishing Ltd.